(untitled) (Journal of Hama University, 2020)
The study was carried out in Abi Jarash Farm, Faculty of Agriculture, Damascus University, during the growing season 2018-2019; to determine the response of nine oats genotypes to different nitrogen fertilization treatments (control: without N fertilization, 100, 150 and 200 kg ha-1) based on some morphological and yield associated traits. The experiment was conduct according to split randomized complete block design (Split-RCBD) with three replications for each treatment and genotype, such as: number of plants per square meter, plant length, number of productive tillers, grain numbers per plant, 1000- kerenel weight, grain yield and harvest index. The results of statistical analysis showed that the treatment 200 kg.ha-1 was superior in all studied traits. The variety Tajikstan was superior in plant length (131.67 cm), number of productive tillers (3.00 tiller.plant-1), grain numbers per plant (122.18 kerenel.plant-1) and grain yield (765.00 g.m-2); while the results indicated that the variety Mexico was superior in number of plants per square meter (333.3 plant.m-2) and harvest index (42.39%). It was also noticed that the variety Romania943 was superior in 1000- kerenel weight (30.95 g).